Anti-Methicillin-Resistant Staphylococcus Aureus and Anti-Methicillin-Sensitive Sstaphylococcus Aureus Effects of Calligonum Comosum l'her. Methanolic Extract - Ahmed Subeh D, Alshrari (2011)
Methicillin Resistant Staphylococcus aureus MRSA is a major life-threatening pathogens causing a variety of serious infections and responsible for the majority of morbidity and mortality in human. Currently, more toxic and more costly antibiotics which are used as last-line agents can only be the choice to cure MRSA infections. Therefore, search for an alternative therapy derived from natural products with effective antimicrobial activity is extensively needed. The aim of this study was to develop a combination therapy for MRSA infection by using naturally derived extract and antibiotic formulation targeting selected infective proteins. The antimicrobial activity of Calligonum comosum methanolic extract (locally known as Arta), a medicinal plant native to Saudi Arabia, was evaluated using Kirby-Bauer disc diffusion method, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC), against gram positive and gram negative pathogens. The activity of the extract was determined for various clones of methicillin-sensitive Staphylococcus aureus (MSSA) and methicillin-resistant Staphylococcus aureus (MRSA). All MSSA and MRSA strains tested were subtyped based on multilocus sequence typing (MLST) and spa typing to differentiate the clones of these strains. Escherichia coli and Klebsiella pneumoniae were included as negative controls. The present study also verified the interactions between 17 commercial antibiotics representing 12 classes and the methanolic extract of C. comosum against MRSA and MSSA strains. The interaction was assessed using a disc-diffusion test performed on agar plates with or without dilution of C. comosum extract at sub-inhibitory concentrations, and the size of the inhibition zones (diameter) were recorded. The bioassay studies revealed that C. comosum extract showed inhibitory activity only to gram positive strains whereas gram negative organisms, Escherichia coli and Klebsiella pneumonia, showed resistant phenotypic pattern to the methanolic extract. In vitro, 10 antibiotics (penicillin, oxacillin, cefoxitin, cloxacillin, ceftriaxone, vancomycin, chloramphenicol, clindamycin, tigecycline and rifampicin) given in combination with the methanolic extract exhibited significant synergistic interaction against most of MRSA and MSSA strains (P= 0.05). Namely 4 antibiotics, rifampicin,vancomycin, cefoxitin and tigecycline (P= 0.00), presented the highest synergism rate with the extract in all MRSA and MSSA strains. These antibiotics when exposed in combination with the C. comosum extract showed greater inhibition zones when compared to the zones by single application of the antibiotics or extract. However, 6 other antibiotics had indifferent effects with the methanolic extract against most of MRSA and MSSA strains, while the extract showed antagonistic interaction with gentamicin. In addition to the bioassay experiments, antimicrobial substance activity of C. comosum extract was elucidated for effect on the changes in DNA repair gene (adaB) sequence in treated S. aureus strains through PCR and RT-PCR assay. The effect of C. comosum extract inhibitory activity on the selected gene sequence showed several nucleotide changes. The detected changes in nucleotides through substitution, insertion or deletion of the nucleotide base pairs in the adaB gene sequence led to several amino acid substitutions at different positions. Nevertheless, to find out the possibility of using the active compounds in the extract as a new alternative antibacterial agent, cytotoxic activity of C. comosum extract was determined using the MTS assay. The toxic effect of the extract was tested on skin fibroblast cells. Various concentrations were selected to evaluate the IC50 of the extract at various time intervals of 24h and 48h, respectively. As shown in vitro, inhibitory action of the extract used is much lower (250 mg/ml) than that reported for antimicrobials (100 mg/ml) derived naturally. Also, identification of crude extract compounds was carried out using gas chromatography-mass spectrometry (GC-MS). GC-MS chromatogram of the given crude sample showed 42 different peaks at various retention times ranging from 5 minutes to 28 minutes for different chemical constituents. GC–MS analysis revealed the presence of 1-((allyloxy)methyl)benzene (18.11%), acetic acid (12.57%), 2-sec-butoxybenzene-1,3-diol (10.61%), formic acid (7.76%), 5-(hydroxymethyl)-2-furancarboxaldehyde (6.67%), 2,3-Dihydro-3,5-dihydroxy-6-methyl-4H-pyran-4-one (5.57%), orthomethoxyphenol (3.71%) and 1-tridecanol (1.27%) as the major components. In conclusion, C. comosum methanolic extract is justified in the present study to be a suitable alternative against MSSA and MRSA based on the inhibiting effect and the low toxicity properties. In addition, the extract in combination with several antibiotics showing synergistic activity further enhances the activity of the extract. The extract also revealed to contain potential antimicrobial chemical compounds. The C. comosum extract warrants further investigation as a drug for anti MRSA and anti MSSA.